(untitled) (STUDIA: JURNAL HASIL PENELITIAN MAHASISWA, 2016)
The background in this study were basis on professionalism in Islamic education the high quality of personal education and his willingness are necessary to support the office duty. This study is a qualitative research, using qualitative descriptive approach which aims to provide a report describing the research results with the data obtained from the data collection techniques used by writers such as interviews, observation, and documentation. While the analysis of data through three stages,namely data reduction, data presentation, and conclusion. The results of this study indicates that the concept of professional competence of teachers in the view of Islam good enough. This has an impact to support the values of professionalism of a teacher, teacher in Islam plays as a holder who carrying double mission at the same time, the religion missions and science missions. In the Islamic perspective, teachers will be successful when doing a good job, have creative thinking, integrated and have the professional competence religious.